Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.4049/jimmunol.176.10.5797
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oligomeric Procyanidins Ameliorate Experimental Autoimmune Encephalomyelitis via Suppression of Th1 Immunity

Abstract: Extracts of Jatoba, a South American herb, when injected i.p. into a mouse model of experimental autoimmune encephalomyelitis (EAE), inhibited the aggravation of clinical symptoms. At the same time, production of myelin oligodendrocyte glycoprotein Ag-specific IFN-γ and TNF-α by spleen cells was markedly suppressed. After administration of Jatoba there was minimal evidence of the demyelination that is characteristic of the EAE model. Decreases in clinical scores were observed when Jatoba extracts were injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
(41 reference statements)
1
31
0
Order By: Relevance
“…We have recently reported that Jatoba bark could alleviate some of the clinical symptoms associated with experimental allergic encephalitis (EAE), an inflammatory demyelinating disease of the central nervous system. 39) We furthermore demonstrated that the active compounds responsible for the biological activity were procyanidins of Jatoba with DP of more than five. The DP value for each oligomer purified by using the present HPLC system corresponds to each mDP value based on thiolysis data.…”
Section: Hplc Protocol Using a Peg Column Enabled Purification Up To mentioning
confidence: 79%
See 1 more Smart Citation
“…We have recently reported that Jatoba bark could alleviate some of the clinical symptoms associated with experimental allergic encephalitis (EAE), an inflammatory demyelinating disease of the central nervous system. 39) We furthermore demonstrated that the active compounds responsible for the biological activity were procyanidins of Jatoba with DP of more than five. The DP value for each oligomer purified by using the present HPLC system corresponds to each mDP value based on thiolysis data.…”
Section: Hplc Protocol Using a Peg Column Enabled Purification Up To mentioning
confidence: 79%
“…The procyanidins from these plants were composed of a variety of flavan-3-ols. 39) In contrast, the profile of Jatoba procyanidins was extremely simple. Furthermore, the interflavanyl linkage was exclusively B-type; an A-type linkage resists thiolysis to give dimeric derivatives 16,18) which were not detected.…”
Section: Jatoba Bark Was Composed Only Of Ec and The Interflavanyl LImentioning
confidence: 99%
“…Furthermore, Th17 cells are implicated in this model and in several other autoimmune diseases. Although some autoimmune responses formerly attributed to Th1 cells are now believed to be mediated by Th17 cells, recent studies [5][6][7][8][9] continue to emphasize the importance of Th1 cells in EAE development. In fact, EAE can be induced by transfer of either Th17 or Th1 cells.…”
Section: Multiple Sclerosis (Ms) Is a T-cell-mediated Inflammatory Aumentioning
confidence: 99%
“…Fr3 was used as HOPC, because this fraction showed the strongest inhibitory activity toward EAE. 19) Thiolysis analysis. To estimate the degree of polymerization of the procyanidins, thiolysis assays were performed by using scaled down versions of previously published methods.…”
Section: Preparation Of Hopcmentioning
confidence: 99%
“…The inhibitory activity of polyphenols is dependent on their degree of polymerization, so that monomer catechin-like green tea polyphenols do not prevent EAE. 19) However, there are reports that green tea polyphenols can ameliorate CIA. 20) In this study, we examined whether procyanidins purified from Jatoba could inhibit CIA, and whether the inhibitory activity would be dependent on polymerization.…”
mentioning
confidence: 99%